Uji aktivitas antihiperurisemia ekstrak daun kopasanda (Chromolaena Odorata (L.) R.M.King & H.Rob terhadap mencit putih jantan (Mus Musculus L.) yang diinduksi kalium oxonat - Asyrun Alkhairi Lubis; Muhammad Yunus; Jefri Naldi; Muhammad Andry; Pricella Ginting; Fira Safitri; Muhammad Amin Nasution (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: Kopasanda leaves (Chromolaena Odorata (L.) R.M.King & H.Rob have been known as medicinal plants and spread in North America, Asia, West Africa and Australia have antibacterial and antioxidant properties, because the active compounds contained in Kopasanda leaves include: alkaloids, flavonoids, steroids, quinone saponins, and tannins. Purpose; This study was to determine the activity of ethanol extract of kopasanda leaves (Chormolaena Odorata (L.) in reducing uric acid levels and to test antihyperuricemia levels and phytochemical screening. Method; This study used a laboratory experimental research design, to extract the chemical content in kopasanda leaves using maceration method using 70% ethanol. This research includes sampling, simplisia making, extract making, phytokimi screening, suspension making, test animal preparation and antihyperuricemia testing. The research data were analyzed using the crucible wallis test statistical test. Result; The study showed a decrease in uric acid levels in the EEDK group 20 mg / BB = 0.86%, EEDK 40 mg / BB = 1.18% and EEDK 80 mg / BB = 2.3%. The results of Wallis' crucial statistical test on day 9 showed a significant difference with a p-value of 0.000. The results of further difference tests showed a significant difference in each treatment. Conclusion: in this study is the ethanol extract of kopasanda leaves (Chromolaena Odorata (L), R.M.King &; H. Rob) the most effective is 80 mg / BB, this is evidenced by the results of one way anova statistical test with a p-value of 0.000 (<0.05).